Contextualising the Hate Speech Debate: the United States and South Africa - Traum, Alexander (Comparative and International Law Journal of Southern Africa, 2022)
This article focuses on two seminal moments that shaped the United States and South Africa’s respective trajectories on the hate speech debate. For the United States, this moment was the so-called New Deal settlement, an informal, unspoken arrangement where the court deferred to Congress in its interpretation of the Constitution’s structural provisions – such as federalism and the separation of powers – while reserving the right to defend individual rights more aggressively. The New Deal settlement created the conditions for the court to enforce the country’s commitment to individual rights via the Bill of Rights on more robust and unapologetic terms. The court’s subsequent approach to hate speech is but an unintended consequence of this New Deal. Coming nearly sixty years after the New Deal, the formation of a constitution ‘based on democratic values, social justice and fundamental human rights’ served as South Africa’s own version of a settlement’. South Africa’s hate speech jurisprudence demonstrates the inherent tension embedded in this settlement, in which the democratic value of speech conflicts with other competing Constitutional values such as dignity and equality. This article examines each country’s hate speech jurisprudence through the prism of these ‘moments’, arguing that the divergence of these systems is a function not merely of the different languages or structure of the two countries’ constitutions, but rather, is born of unique historical and cultural contexts.